Outdoor experimental and numerical simulation of photovoltaic cooling using porous media - Masalha, I.; Masuri, S.U.; Badran, O.O.; Ariffin, M.K.A.M.; Abu Talib, A.R.; Alfaqs, F. (Elsevier, 2023)
The electrical power production through photovoltaic panels has become essential, due to high demand for electrical power supply worldwide to cope with new technological developments, but these PV cells are affected by the temperature rise on the back surface during their operation, which decreases their electrical power and reduces their performance. Therefore, photovoltaic back surface temperature must be kept as low as possible. In this study, the cooling processes using porous media (gravel) of different porosities such as 0.35, 0.4, and 0.48 were tested at different flow rates. Accordingly this study was divided into three scenarios: The first scenario the porous media having a porosity of 0.35 (case I) were compared with water case (case II) without any porosity and with uncooling case (case III). In the second scenario, three channels were filled with different porosities (i.e. 0.35, 0.4 and 0.48) (i.e. case I, case IV, case V) and compared with the uncooled case III. While in the third scenario, three channels filled with porous media of the same porosity of 0.35, but at different flow rates (i.e. 1 L/min, 2 L/min, and 3 L/min) (case a, case b, case c) were tested. Based on the results, the lowest photovoltaic surface temperature was reduced approximately to 35.7 while the power output increased to 9.4 at volume flow rate of 3 L/m and porosity of 0.35 (case c), and also there was an agreement between the experimental and numerical results. Through the mathematical equation, the effect of Nusselt number, Reynolds number, Prandtl number and porosity on the heat transfer coefficient and the effect of water entry velocity, porosity and gravel diameter on pressure drop was found.